Imaging-Based Screening Platform Assists Protein Engineering - Fabritius, Arne; Ng, David; Kist, Andreas M.; Erdogan, Mutlu; Portugues, Ruben; Griesbeck, Oliver (Cell Chemical Biology, 2018)
Protein evolution requires generation and screening of large numbers of variants. To expedite screening, Fabritius et al. built a platform that integrates fluorescence-based image analysis and picking of bacterial colonies. They engineered mCarmine, a far-red-emitting fluorescent protein for tagging and deep tissue imaging.
CRIS-Team Scopus Importer:2021-04-12
Keywords: directed evolution; fluorescent proteins; image analysis; protein engineering; screening